Assessing Adherence to Annual Dilated Eye Exam Recommendations in Patients with Diabetes and Erectile Dysfunction - Ethan Greenberg; Lisa A Hark; Christine Hubert; Brianna Kenney; Courtney B Reamer; Julia A Haller; Robert Bailey; Irvin Hirsch (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
Aims: This prospective, observational, pilot study assessed adherence rates of annual dilated fundus examinations (DFEs) among patients with diabetes mellitus (DM) and erectile dysfunction (ED) in a university-based practice and identified predictors associated with DFE adherence. Methods: A total of 56 men who had been diagnosed with ED and type I or type II DM were enrolled in the study and given a 24-question survey assessing their knowledge of DFE recommendations and ocular history. Patients were classified as adherent (n=39) or non-adherent (n=17) to the annual DFE. The differences in demographics, baseline characteristics, and survey responses between the adherent and non-adherent groups were analyzed using Fisher's exact test for the comparison of proportions and Student's t-test for the comparison of means. Results: The adherent group was more likely than the non-adherent group to be seeing an eye doctor (p=0.03). The most common cited reasons for not seeing an ophthalmologist were "Too busy" (n=5) and "Unable to pay the co-pay" (n=4). Conclusions: Patients with ED and DM showed a greater adherence to annual DFE recommendations than those in the reported non-ED population. Minimizing the cost barrier and educating about diabetes complications may increase adherence in obtaining a DFE.